2019
DOI: 10.1371/journal.pone.0218029
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of Ogura cytoplasmic male sterility-related genes in turnip (Brassica rapa ssp. rapifera) using RNA sequencing analysis and bioinformatics

Abstract: Ogura-type cytoplasmic male sterility (Ogura-CMS) has been widely used in the hybrid breeding industry for cruciferous vegetables. Turnip ( Brassica rapa ssp. rapifera ) is one of the most important local cruciferous vegetables in China, cultivated for its fleshy root as a flat disc. Here, morphological characteristics of an Ogura-CMS line ‘BY10-2A’ and its maintainer fertile (MF) line ‘BY10-2B’ of turnip were investigated. Ogura-CMS turnip showed a reduction in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 115 publications
0
22
0
Order By: Relevance
“…Thus, we assayed 6 RNA-Seq datasets from B. rapa male-sterile mutants [26,28], GMS [29,30] and CMS [27,31] lines, and found that 9 BrPERK genes were downregulated in at least five MS lines (Fig. 6a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, we assayed 6 RNA-Seq datasets from B. rapa male-sterile mutants [26,28], GMS [29,30] and CMS [27,31] lines, and found that 9 BrPERK genes were downregulated in at least five MS lines (Fig. 6a).…”
Section: Discussionmentioning
confidence: 99%
“…Seven raw RNA-Seq datasets of B. rapa plant were obtained from the NCBI Gene Expression Omnibus (GEO) and Sequence Read Archive (SRA) [26][27][28][29][30][31]60]. One of these datasets consisted of the genome-wide transcriptomes of tissues [60], and the other six datasets consisted of the transcriptomes of male-sterile lines, including two male-sterile mutants [26,28], two GMS lines [29,30] and two ogu-CMS lines [27,31]. These male-sterile lines are no pollen phenotype and their anther abortion occurs during the tetrad period.…”
Section: Rna-seq Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, advancement in molecular technology, has enabled breeders and molecular researchers to identify various plant transcription factors, genes and explore protein expression at the translational, transcriptome and proteome level, such as the CMS studies of the Chinese cabbage (5) , turnip (6) , Cucumis melo L. (7) , cotton (8, 9) , rice (10) , Brassica napus L. (11) . Transcriptomic analysis in cotton (CMS-D8) revealed that the reactive oxygen species (ROS) were released from mitochondria and served as important signal molecules in the nucleus, causing the formation of abnormal tapetum (8) .…”
Section: Introductionmentioning
confidence: 99%
“…Previously, an Ogura-CMS line 'BY10-2A' and its maintainer fertile (MF) line 'BY10-2B' of turnip (B. rapa ssp. rapifera) were characterized [52]. Mutation of mitochondrial orf138 retroregulates the expression of nuclear genes, and interactions between them are responsible for male sterility in Ogura-CMS turnip.…”
Section: Introductionmentioning
confidence: 99%